WAYANG KULIT SEBUAH TEATER BONEKA BALI - I Made Sudana (Paraguna, 2018)
Wayang kulit  Bali  are  one  of the  Balinese puppet art forms  that  still survive  today. This  art has  undergone innovation  according to the  times.  Among the  striking forms of innovation  in the field  of music accompaniment,  which originally used  4 pieces of gender wayang or gamelan bebatelan,   but  now accompanied  by gamelan  semar pagulingan or gamelan  balaganjur  which is  a  middle class  bali  music ensemble. Besides that,  presenting  vocal  is  the  dalang,   but  now it  has   been added  to  the accompaniment  of gerongan,   namely  the  choir  of a  group  of female  singers  and wra suara.